Investigating EFL Teachers’ Readiness To Use Generative AI For Teaching English At Junior High School In Buleleng District - Luh Feni Lestari; Made Hery Santosa; Anak Agung Gede Yudha Paramartha (CV. Ulil Albab Corp, 2026)
The rapid development of Generative Artificial Intelligence (GenAI) in the era of Industry 4.0 has accelerated its integration into education, including Teaching English as a Foreign Language (TEFL). Despite its potential benefits, teachers’ readiness to integrate GenAI remains questionable. Therefore, this study aimed to investigate the readiness of junior high school English teachers in Buleleng District in using GenAI. This research applied an explanatory sequential mixed-method design, beginning with a survey adapted from the Readiness for Artificial Intelligence Applications Scale (RAIS), followed by in-depth interviews to elaborate on the quantitative findings. The results indicate that teachers tended to be ready to use GenAI, particularly in terms of technological self-efficacy and instructional use. However, regarding ethical awareness, many teachers were still unclear about appropriate ethical principles and boundaries in using AI. These findings highlight the need to strengthen ethical literacy and provide continuous professional development to ensure responsible GenAI integration in classrooms.